TO STUDY THE QUALITATIVE ANALYSIS AND IMAGES OF HINGUL DURING THE SHODHAN PROCESS - Ajay Bapusaheb, *Sonawane; Devyani Deodatta, Bhadlikar; Mahendra Tryambaklal, Mehta; Suryavanshi, Nilesh; Vedvati, Bhapkar (International Journal of Ayurveda and Pharma Research, 2015)
Rasaacharya were well known about the toxic effect produce due to use of mineral in their impure form. For removing this toxic effect they mentioned various Shodhan (purification) processes in their books. Shodhan process plays a very significant role in purification of Rasa dravya like Hingul for internal administration. In this study Shodhan of Hingul by Kshalan process is performed which is mentioned in book of Rasatarangini. Because of the need of purification & standardization in Ayurveda we do ICP-AES for Elemental qualitative analysis and FEG-SEM for images.After doing ICP-AES test there are elements like Yttrium (Y), Zirconium (Zr), Vanadium (V), Ytterbium (Yb), in the sample of first Kshalan water, which were done after completion of seven Bhavana. These elements were not found in the sample of Raw Hingul and sample of after seven Bhavana of Hingul. After doing repeated Kshalan process these elements were not found in any sample except the first Kshalan water sample. In the water sample of first Kshalan, found 23 elements and after the seven Kshalan, and got only 16 elements. Hence the impurities may be removed after the Kshalan process.After doing a FEG-SEM test we found there are changes in the images and particle in each step of Shodhan process of different samples. Because of continuous Bhavana particle size were reduced.